2022
DOI: 10.3390/curroncol29070366
|View full text |Cite
|
Sign up to set email alerts
|

Can Radiotherapy Empower the Host Immune System to Counterattack Neoplastic Cells? A Systematic Review on Tumor Microenvironment Radiomodulation

Abstract: Despite the rising evidence in favor of immunotherapy (IT), the treatment of oncological patients affected by so-called “cold tumors” still represents an open issue. Cold tumors are characterized by an immunosuppressive (so-called cold) tumor microenvironment (TME), which favors host immune system suppression, cancer immune-escape, and a worse response to IT. However, the TME is not a static element, but dynamically mutates and can be changed. Radiotherapy (RT) can modulate a cold microenvironment, rendering i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Emerging data have established RT as a useful therapeutic option also for oligometastatic and oligorecurrent/oligoprogressive disease [16], rare histologies [17,18], or in combination with new drugs available for hormone-sensitive and castration-resistant PC. In recent years, advances in radiation planning and delivery techniques, in particular the advent of new-generation linac with the FFF mode, have improved treatment accuracy and given rise to the adoption of ultrahypofractionated radiation schedules in the form of SBRT [19] in different oncological settings, with acceptable toxicity [20][21][22][23][24][25]. Despite this, local failure after RT still remains a critical issue.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have established RT as a useful therapeutic option also for oligometastatic and oligorecurrent/oligoprogressive disease [16], rare histologies [17,18], or in combination with new drugs available for hormone-sensitive and castration-resistant PC. In recent years, advances in radiation planning and delivery techniques, in particular the advent of new-generation linac with the FFF mode, have improved treatment accuracy and given rise to the adoption of ultrahypofractionated radiation schedules in the form of SBRT [19] in different oncological settings, with acceptable toxicity [20][21][22][23][24][25]. Despite this, local failure after RT still remains a critical issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, this inflammatory response induced by SBRT may not be durable since an immunosuppressive cascade can also be triggered by SBRT. 30 31 One such mechanism is generating immunosuppressive adenosine from extracellular ATP released from irradiated tumor cells. We demonstrated that systemic administration of anti-CD73 and anti-PD-L1 greatly augmented local SBRT-induced antitumor efficacy in both mouse orthotopic and metastatic models.…”
Section: Discussionmentioning
confidence: 99%
“…This may happen because tumor-antigen release induced by radiations can activate an immune response directed against the antigen itself [ 53 , 54 ]. The addition of radiotherapy to immunotherapy allows for the boosting of the immune system, stimulating the release of immunogenic tumor-specific antigens and depleting intratumoral T regs , thus encouraging the idea that the combination of radiotherapy with immunotherapy may strengthen the anti-tumor immune response both locally and systemically (the so-called abscopal effect) [ 55 , 56 ].…”
Section: Combining Immunotherapy and Ionizing Radiation For Sclcmentioning
confidence: 99%